(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article explores the challenges faced by modern linguistics and translation studies in the rapidly evolving digital age. It proposes a comprehensive, technology-driven approach to address these issues, focusing on the integration of artificial intelligence, machine learning, and natural language processing. The study employs a mixed-methods approach, combining qualitative analysis of existing literature with quantitative data from recent experiments in computational linguistics. The article concludes by outlining a roadmap for future research and implementation, emphasizing the need for collaboration between linguists, computer scientists, and industry stakeholders.